Economic Globalization and Human Development in Bangladesh - Moon, Jannat Sharmin; Pande, Saikat; Haque, Md. Fazlul (South Asian Journal of Social Sciences and Humanities, 2024)
Economic globalization has garnered significant scholarly interest due to its potential to contribute to social stability and economic development. In recent years, there has been a growing emphasis on human development indicators in the context of Bangladesh's economic progress. This research examines the impact of economic globalization on the HDI of Bangladesh, focusing on the indicators of foreign direct investment (FDI), foreign assistance, and personal remittance inflow. Using an autoregressive distributed lag (ARDL) model and fully modified ordinary least squares (FMOLS) estimates, the research finds that not all globalizing variables have a linear effect on Bangladesh's HDI. The empirical results also suggest that the impact of economic globalization on HDI varies across the different dimensions of human development. Short-term association between foreign assistance is rather high. There is a long-term, positive correlation between FDI and foreign assistance. The research offers some policy recommendations to address the challenges of economic globalization and human development in Bangladesh. These include: Investing in education and healthcare to improve the skills and productivity of the workforce, implementing social safety nets to protect vulnerable groups from the negative effects of globalization, ensuring equitable distribution of resources to ensure that everyone benefits from the benefits of globalization, promoting inclusive growth by supporting small and medium-sized enterprises and creating jobs in the informal sector. The research concludes that a balanced approach to economic globalization is essential to maximize the benefits for human development in Bangladesh.
Keywords: Economic Globalization, Economic Development, Human Development, Foreign Direct Investment, Personal Remittance Inflow